Comparative study on surface states and CO gas sensing characteristics of CuO thin films synthesised by vacuum evaporation and sputtering processes. (January 2022) - Mahana, Debashrita; Mauraya, Amit Kumar; Pal, Prabir; Singh, Preetam; Muthusamy, Senthil Kumar
Highlights: Polycrystalline CuO thin films have synthesized with thermal oxidation of cu metal films deposited by two PVD techniques, i.e. vacuum evaporation and DC sputtering. CuO film obtained by sputtering process has a granular surface morphology with relatively smaller grains than that obtained with vacuum evaporation. A comparatively larger presence of Cu 2+ ions is observed on the surface of sputtered CuO films, which plays a critical role in CO gas adsorption. CuO film prepared by sputtering process exhibits 15∼20% higher sensitivity towards CO gas with a faster response than vacuum evaporated film. Abstract: CuO thin films have been synthesised by thermal oxidation of Cu films deposited using vacuum evaporation and sputtering processes. Single-phase polycrystalline CuO thin films with monoclinic crystalline structure and porous granular surface morphology are obtained by thermal oxidation of Cu films at 400 °C for 5 h, as characterized by x-ray diffraction and scanning electron microscopy. X-ray photoelectron spectroscopy revealed a relatively larger presence of Cu 2+  ions on the surface of sputtered CuO film compared to the evaporated film. The CuO film synthesised by sputtering process exhibits 15~20 % higher sensing response towards 91 and 915 ppm concentrations of CO gas than that prepared with vacuum evaporation process. The better CO sensing characteristics of sputtered CuO film are understood based on the combined effects of smaller crystallite size, finer granular surface morphology and higher surface presence of Cu 2+  ions as compared to CuO film synthesised by vacuum evaporation process. Graphical abstract: Image, graphical abstract